Inflammatory bowel disease‐specific pregnancy knowledge of gastroenterologists against general practitioners and obstetricians. Issue 5 (1st October 2015) - Kashkooli, Soleiman B; Andrews, Jane M; Roberts, Matthew B; Selinger, Christian P; Leong, Rupert W
Abstract : Background: Patients with inflammatory bowel disease (IBD) tend to have smaller family sizes. Health care professionals (HCPs) may inadvertently provide inaccurate advice to patients resulting in voluntary childlessness or unfavourable pregnancy outcomes. Objective: The study aims to objectively measure IBD‐specific pregnancy‐related knowledge of general practitioners (GPs) and obstetricians/gynaecologists (OB/GYNs) in comparison with gastroenterologists (GEs) using the validated Crohn's and Colitis Pregnancy Knowledge (CCPKnow) questionnaire. Methods: GPs, OB/GYNs and GEs in two Australian states completed the CCPKnow (range 0–17) and demographic questionnaires. The CCPKnow addresses issues pertaining to conception, IBD inheritance, risk of congenital abnormalities, medication use in the peri‐conceptual period, pregnancy and breastfeeding, and mode of delivery. Results: In total, 337 HCPs responded. GPs ( n  = 188/2086) and OB/GYNs ( n  = 94/228) had significantly lower knowledge than GEs ( n  = 55/165) for the composite CCPKnow (medians 11, 13 and 17, respectively, p  < 0.001), and almost all domains. GEs were the only group to attain a median CCPKnow score in the top category (14–17). More than 70% of GPs and OB/GYNs expressed discomfort with initiation of IBD medications around conception/pregnancy. GPs (43.6%) and OB/GYNs (45.7%) perceived thiopurine use to be unsafe during pregnancy and to cause serious harm to the baby. Conclusions: Our study demonstrates that GPs and OB/GYNs have inadequate and variable IBD‐specific pregnancy‐related knowledge including use of IBD medications. These results support the need for GEs' prime role in a team‐based management for IBD patients who are pregnant or planning pregnancy.